Effect of species, pretreatments, and drying methods on the functional and pasting properties of high‐quality yam flour. Issue 1 (20th July 2015) - Wahab, Bashirat A.; Adebowale, Abdul‐Rasaq A.; Sanni, Silifat A.; Sobukola, Olajide P.; Obadina, Adewale O.; Kajihausa, Olatundun E.; Adegunwa, Mojisola O.; Sanni, Lateef O.; Tomlins, Keith
Abstract: The study investigated the functional properties of HQYF (high‐quality yam flour) from tubers of four dioscorea species . The tubers were processed into HQYF using two pretreatments (potassium metabisulphite: 0.28%, 15 min; blanching: 70°C, 15 min) and drying methods (cabinet: 60°C, 48 h; sun drying: 3 days). Significant differences ( P < 0.05) were observed in pasting characteristics of flours among the four species. The drying method significantly affected only the peak viscosity. The interactive effect of species, pretreatment, and drying methods on the functional properties was significant ( P < 0.05) except for emulsification capacity, angle of repose, and least gelation concentration. The significant variation observed in most of the functional properties of the HQYF could contribute significantly to breeding programs of the yam species for diverse food applications. The pastes of flour from Dioscorea dumetorum pretreated with potassium metabisulphite and dried under a cabinet dryer were stable compared to other samples, hence will have better applications in products requiring lower retrogradation during freeze/thaw cycles. Abstract : The functional properties of HQYF (high‐quality yam flour) from tubers of four dioscorea species were investigated. The significant variation recorded in most of the functional properties of the HQYF could contribute significantly to breeding programs of the yam species for diverse food applications. The pastes of flour from Dioscorea dumetorum were stable compared to other samples, hence will have better applications in products requiring lower retrogradation during freeze/thaw cycles.